2017
DOI: 10.3389/fphys.2017.00409
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation in Young and Healthy Subjects Is More Sensitively Identified by Higher Frequencies of Electrodermal Activity than by Skin Conductance Level Evaluated in the Time Domain

Abstract: We analyzed multiple measures of the autonomic nervous system (ANS) based on electrodermal activity (EDA) and heart rate variability (HRV) for young healthy subjects undergoing 24-h sleep deprivation. In this study, we have utilized the error awareness test (EAT) every 2 h (13 runs total), to evaluate the deterioration of performance. EAT consists of trials where the subject is presented words representing colors. Subjects are instructed to press a button (“Go” trials) or withhold the response if the word pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…Other researchers found a moderate correlation of spectral indices of HRV with participants' performance in PVT during sleep deprivation (Chua et al, 2012). In our previous study (Posada-Quintero et al, 2017), few significant differences were found in HRV parameters throughout the experiment. Only HRVLF exhibited a significant increase after 20 hours.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Other researchers found a moderate correlation of spectral indices of HRV with participants' performance in PVT during sleep deprivation (Chua et al, 2012). In our previous study (Posada-Quintero et al, 2017), few significant differences were found in HRV parameters throughout the experiment. Only HRVLF exhibited a significant increase after 20 hours.…”
Section: Discussionmentioning
confidence: 47%
“…However, those studies did not explore the occurrence of rapid shifts (usual in the EDA signal) but focused only on the changes in SCL (low components of the signal). In a previous study, we found significant changes in the higher frequency components of EDA after 18 hours of sleep deprivation (Posada-Quintero et al, 2017). Hence, we expect that changes in the higher frequencies of the EDA signal correlate with the observed deterioration of participant performance resulting from prolonged wakefulness.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations